Is a modified Global Trigger Tool method using automatic trigger identification valid when measuring adverse events?: A comparison of review methods using automatic and manual trigger identification. (8th October 2018) - Mevik, Kjersti; Hansen, Tonje E; Deilkås, Ellen C; Ringdal, Alexander M; Vonen, Barthold
Abstract: Objectives: To evaluate a modified Global Trigger Tool (GTT) method with manual review of automatic triggered records to measure adverse events. Design: A cross-sectional study was performed using the original GTT method as gold standard compared to a modified GTT method. Setting: Medium size hospital trust in Northern Norway. Participants: One thousand two hundred thirty-three records selected between March and December 2013. Main outcome measure: Records with triggers, adverse events and number of adverse events identified. Recall (sensitivity), precision (positive predictive value), specificity and Cohen's kappa with 95 % confidence interval were calculated. Results: Both methods identified 35 adverse events per 1000 patient days. The modified GTT method with manual review of 658 automatic triggered records identified adverse events ( n = 214) in 189 records and the original GTT method identified adverse events ( n = 216) in 186 records. One hundred and ten identical records were identified with adverse events by both methods. Recall, precision, specificity and reliability for records identified with adverse events were respectively 0.59, 0.58, 0.92 and 0.51 for the modified GTT method. The total manual review time in the modified GTT method was 23 h while the manual review time using the original GTT method was 411 h. Conclusions: The modified GTT method is as good as the original GTT method that complies with the GTTs aim monitoring the rate of adverse events. Resources saved by using the modified GTT method enable for increasing the sample size. The automatic trigger identification system may be developed to assess triggers in real-time to mitigate risk of adverse events.